2021
DOI: 10.1186/s13063-021-05242-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of N-Acetylcysteine in severe COVID-19 patients: A structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives Severe acute respiratory infection (SARI) caused by the SARS-CoV-2 virus may cause lung failure and the need for mechanical ventilation. Infection with SARS-COV-2 can lead to activation of inflammatory factors, increased reactive oxygen species, and cell damage. In addition to mucolytic effects, N-Acetylcysteine has antioxidant effects that we believe can help patients recover. In this study, we evaluate the efficacy of N-Acetylcysteine in patients with severe COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Nevertheless, in a phase III controlled randomized clinical trial with patients diagnosed with severe COVID-19, supplementation of intravenous NAC associated with standard treatment is being carried out, where the authors believe that, in addition to exerting a mucolytic effect, NAC will be able to help in patient recovery through its antioxidant effects (IRCT20200509047364N3, at Iranian Registry of clinical trials) [ 184 ].…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…Nevertheless, in a phase III controlled randomized clinical trial with patients diagnosed with severe COVID-19, supplementation of intravenous NAC associated with standard treatment is being carried out, where the authors believe that, in addition to exerting a mucolytic effect, NAC will be able to help in patient recovery through its antioxidant effects (IRCT20200509047364N3, at Iranian Registry of clinical trials) [ 184 ].…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…Another attractive approach to hamper excessive VWF large multimers binding to platelets and the ensuing microthrombosis could be the use of novel thrombotic thrombocytopenic purpura treatments caplacizumab [ 177 ] or anfibatide [ 178 ], both of which inhibit binding of the platelet receptor GPIX-Ib to VWF. Moreover, treatment with N-acetyl cysteine, known to reduce the size of VWF multimers, could also be a useful, easy, and cheap strategy in COVID-19 [ 179 ].…”
Section: Microthrombosis and Mechanisms Of Vascular Damage In Covid-19mentioning
confidence: 99%
“…Yet, in agreement with most other studies, the results of the present study confirmed the relationship between administration of interferon and patient recovery. In comparison, considering the effects of different medication groups such as nonsteroidal anti-inflammatory medications like ibuprofen, or medications such as famotidine or N-acetylcysteine, which are effective in managing the inflammatory phase in patients with moderate to severe COVID-19, paying particular attention to the effect of antivirals (with virus-specific action) is highly important in patients with COVID (14)(15)(16).…”
Section: Dear Editormentioning
confidence: 99%